2014
DOI: 10.1634/theoncologist.2014-0178
|View full text |Cite
|
Sign up to set email alerts
|

6-Thioguanine: A Drug With Unrealized Potential for Cancer Therapy

Abstract: Sixty years ago, 6-thioguanine (6-TG) was introduced into the clinic. We suggest its full potential in therapy may not have been reached. In this paper, we contrast 6-TG and the more widely used 6-mercaptopurine; discuss 6-TG metabolism, pharmacokinetics, dosage and schedule; and summarize many of the early studies that have shown infrequent but nevertheless positive results with 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 38 publications
1
57
0
Order By: Relevance
“…Inhibitors identified in virtual screening included Food and Drug Administration-approved drugs used to treat cardiovascular disease, certain types of cancer, autoimmune diseases, anorexia, cachexia, and weight loss associated with cancer and AIDS (1, 4850). Emerging evidence indicates that in addition to regulating insulin signaling, cytoskeleton remodeling, and receptor endocytosis (51), SHIP2 is implicated in the development and progression of certain types of cancer (52).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors identified in virtual screening included Food and Drug Administration-approved drugs used to treat cardiovascular disease, certain types of cancer, autoimmune diseases, anorexia, cachexia, and weight loss associated with cancer and AIDS (1, 4850). Emerging evidence indicates that in addition to regulating insulin signaling, cytoskeleton remodeling, and receptor endocytosis (51), SHIP2 is implicated in the development and progression of certain types of cancer (52).…”
Section: Discussionmentioning
confidence: 99%
“…Up to the present, hundreds of 6MP and 6TG related studies have been published every year, including metabolism, pharmacokinetics and dosage as well as their use in various therapies that target cancers, rheumatoid arthritis, systemic lupus erythematosus and Crohn's disease (Karran and Attard, 2008). 6TG has recently been proposed as a means of treating a wide variety of cancers that have a high frequency of homozygous deletion of the gene encoding methylthioadenosine phosphorylase, which include leukemia, glioblastoma, lung cancer, pancreatic, squamous cell carcinoma and others (Munshi et al, 2014). In addition, 6MP and its pro-drug, azathioprine, have also been used for many years as an immunosuppressant when treating organ transplant recipients (Karran and Attard, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One report showed that MTAP abrogates phosphoribosylation conversion of 6‐TG to a toxic derivative (Munshi et al ., 2014). Interestingly, another report revealed that the p16 gene is often lost along with the MTAP gene in pancreatic cancer (Lubin and Lubin, 2009; Munshi et al ., 2014). RT‐PCR and Western blot analysis indicated that MTAP was expressed in HPDE and 34 629 cells (which showed the highest IC 50 among four PDAC cell lines; Fig.…”
Section: Resultsmentioning
confidence: 99%